Proving woman : female spirituality and inquisitional culture in the later Middle Ages - Elliott, Dyan, 1954- (Princeton University Press, 2004)
Around the year 1215, female mystics and their sacramental devotion were among orthodoxy's most sophisticated weapons in the fight against heresy. Holy women's claims to be in direct communication with God placed them in positions of unprecedented influence. Yet by the end of the Middle Ages female mystics were frequently mistrusted, derided, and in danger of their lives. The witch hunts were just around the corner. While studies of sanctity and heresy tend to be undertaken separately, Proving Woman brings these two avenues of inquiry together by associating the downward trajectory of holy wom.